Etiologic characteristics revealed by mNGS-mediated ultra-early and early microbiological identification in airway secretions from lung transplant recipients - Zhang, Xiaoqin; Tang, Xuemei; Yi, Xiaoli; Lei, Yu; Lu, Sen; Li, Tianlong; Yue, Ruiming; Pan, Lingai; Feng, Gang; Huang, Xiaobo; Wang, Yiping; Cheng, Deyun (Frontiers in Immunology, 2023)
half (72.73%), with gram-positive and -negative bacteria occupying large proportions.Fungi such as Candida are also frequently detected. 5 (50%) microbial species identified by microbial culture had multiple drug resistance (MDR). Within one month, 26 (68.42%) recipients got infected (with a median time of 9 days), among which 10 (38.46%) cases were infected within one week. In the infected recipients, causative agents were detected in advance by mNGS in 9 (34.62%) cases, and most of them (6, 66.67%) were infected within one week (ultra-early). In the infection that occurred after one week, the consistency between mNGS results and the etiological agents was decreased.Conclusions Based on the mNGS-reported pathogens in airway secretions samples collected two hours, the initial empirical anti-infection regimes covering the bacteria and fungi are reasonable. The existence of bacteria with MDR forecasts the high risk of infection within 48 hours after transplant, reminding us of the necessity to adjust the antimicrobial strategy. The predictive role of mNGS performed within two hours in etiological agents is time-limited, suggesting continuous pathogenic identification is needed after lung transplant.